Analisa data Untuk Menentukan Kelulusan Proposal Penelitian Dosen internal STMIK Triguna Dharma Menggunakan Metode Analytical Hierarchy Proses (AHP) - Ayu Ofta Sari Ayu; Sri Wahyuni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
he selection process for lecturer research proposals at STMIK Triguna Dharma is often faced with challenges in objective and transparent assessment. This is due to the high number of proposals submitted and the variety of criteria that need to be considered, such as scientific contribution, innovation, relevance and implementation potential. This research aims to develop a more objective selection model by applying the Analytical Hierarchy Process (AHP) method in determining the feasibility of lecturer research proposals. The AHP method is used because of its ability to break down complex problems into a hierarchical structure and calculate the priority weights of each assessment criterion. This research process begins with identifying the main criteria and sub-criteria, followed by collecting data from research proposals, expert interviews, and literature studies. Each criterion is evaluated through a pairwise comparison matrix to obtain objective priority weights. Next, all research proposals are assessed based on the weight of the criteria and ranked to determine the most feasible proposal. The research results show that the criteria for scientific contribution and relevance to institutional goals have the highest weight in the assessment, making them the main aspects in the proposal selection process at STMIK Triguna Dharma. With the AHP method, this research concludes that the proposal selection process can be carried out more systematically, transparently and fairly. The implementation of this model is expected to be able to help institutions fund research that is most relevant and has a significant impact in accordance with the campus' vision and mission. Keywords: Lecturer research; Analytical Hierarchy Process; Data analysis; Matrix; Ranking